The Relationship Between Elderly Knowledge and the Incidence of Gout in Blangreuling Village, Bireuen Regency - Sri Wahyuni; Firayani, Firayani; Zainab, Zainab; Mutia, Mutia; Ayu Sabila; Nova Eliza; Dek Opra; Rini Fitriani; Khairul Moliza; Lutvia Humaira; Eliana, Eliana (Jurnal EduHealth, 2025)
Uric acid, or gout, is a form of inflammatory arthritis caused by the accumulation of monosodium urate crystals in the joints. This buildup occurs due to increased uric acid levels in the blood (hyperuricemia), which can result from excessive uric acid production or inefficient excretion through the kidneys. This study aims to determine the relationship between elderly knowledge and the incidence of gout in Blangreuling Village. The research employs a cross-sectional design and involves elderly individuals in Blangreuling Village. The total population consists of 36 people, with the sample also comprising 36 individuals using a total sampling technique. Data was collected through questionnaires and secondary data, then analyzed using descriptive analysis to identify the relationship between elderly knowledge and gout incidence. The study results show that 22 elderly individuals (61.11%) have good knowledge, while 14 individuals (38.88%) have less knowledge. Additionally, 20 elderly individuals (55.55%) were diagnosed with gout. Bivariate analysis results indicate a significant relationship between knowledge and gout incidence (p < 0.05). This study is expected to contribute to a better understanding of gout among the elderly in rural communities and inform targeted public health interventions, as well as the development of effective prevention and management strategies for gout in the elderly population of Blangreuling Village.